Response to thrombolytic agents in acute myocardial infarction in opium abusers versus non-abusers - Seyed Mohammad Hashemi Jazi; Idin Ahang Nazary; Mohaddeseh Behjati (Wolters Kluwer Medknow Publications, 2012)
Objective: Coronary artery disease is one of the leading causes of morbidity and mortality in populations. In opium abusers, level of circulating coagulation factors differs from non-abusers. The aim of this study was to evaluate response to thrombolytic therapy in opium abusers vs. non-abusers. Methods: In this prospective observational study, 83 patients (36 opium abusers and 47 non-abusers) with AMI were evaluated for the presence and degree of response to thrombolytic agent. All patients were monitored for electrocardiographic changes and response to thrombolysis 2 hours before and after administration of thrombolytic agent. Serum CPK and LDH were measured 2 hours before and after thrombolysis. Quantitative and qualitative data were analyzed by independent t-test and chi-square using SPSS, respectively. Findings: ST-resolution 2 hours after thrombolysis was 63.8% and 44.4% in opium users and non-users, respectively. Serum level of CPK cardiac biomarker 2 hours after thrombolysis was 980 ± 245 and 847 ± 130 IU/L in opium users and non-users, respectively. Conclusion: Our data demonstrate that in those patients with opium abuse, electrocardiographic changes after thrombolysis were significantly lower than opium non-users (P < 0.05). Opium users showed better ST-resolution compared with non-users. Opium addiction had effect on cardiac enzymes despite their effect on response to streptokinase.